Effect of low and high pulsed electric field processing on macro and micro minerals in beef and chicken. (February 2018) - Khan, Ammar Ahmad; Randhawa, Muhammad Atif; Carne, Alan; Mohamed Ahmed, Isam A.; Al-Juhaimi, Fahad Y.; Barr, David; Reid, Malcolm; Bekhit, Alaa El-Din A.
Abstract: The present study investigated the effects of low pulsed electric field (LPEF, 2.5 kV, 200 Hz and 20 μs) and high pulsed electric field (HPEF, 10 kV, 200 Hz and 20 μs) on the levels of 40 macro- and micro-minerals in raw and cooked cold-boned beef loins at 1 and 14 days of post-treatment and in chicken breasts at 1 and 4 days. PEF treatment reduced the concentration of Ca (P < 0.01), Na (P < 0.001) and Mg (P < 0.03) and increased the concentration of Cr (P < 0.01) in beef compared to non-treated controls. HPEF chicken breast treated samples had significantly (P < 0.001) higher Ni concentration than LPEF and control samples that were not different from both treatment groups. Both LPEF and HPEF treated chicken samples had higher Cu concentrations than control samples. The results suggest that PEF treatment of meat can result in the release of elements from the PEF electrodes and contribute to the mineral status of beef and chicken meat samples. PEF appears to have a differential effect on mineral content according to the type of meat. The nutritional and safety consequences of these effects need to be evaluated. Highlights: Effect of low PEF (LPEF) and high PEF (HPEF) on the levels of 40 minerals in beef and chicken is reported. PEF reduced the concentration of Ca, Na and Mg and increased the concentration of Cr in beef. HPEF treated chicken breasts had higher Ni concentration than LPEF and control. Both LPEF and HPEF treated chicken breasts had higher Cu concentrations than control samples. Results suggest potential release of minerals from PEF electrodes.